Impact of Accelerating the Export of Nickel Prohibition on Non-Tax Revenue and National Economy - Rizky Ikhsan Rahadian; Muhammad Ramdhan Ibadi (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2021)
The discourse on the acceleration of the nickel export ban put forward by the Indonesian Government in August 2019 triggered various reactions and responses from market players in various countries. This can happen considering that Indonesia in recent years has contributed significantly to the international nickel trade. This study aims to look at the impact of implementing the policy on the receipt of PNBP royalties in nickel mining as well as the economy as broadly indicated in indicators of output, income, profit, and tax. This study uses a descriptive method with a simulation approach and a quantitative model of the BPS input-output table in 2010. The results of this study indicate that the country has the potential to lose nickel royalty PNBP of Rp 240-372 billion due to the absence of export of raw nickel ore. However, this loss can be replaced if the existing nickel smelter can operate optimally and the construction of additional smelter is realized according to plan. Even so, there is a risk of a decrease in the supply of nickel ore for smelters due to the preference of miners to export nickel ore at more attractive prices, which in turn can reduce economic value along the production chain. Therefore, the Government needs to establish communication with various business actors in order to improve the trade system to ensure supply and continue to encourage the realization of smelter construction.